Perhitungan Angka Lempeng Total Bakteri Jamu Kunyit Asam di Kayuringin Jaya Kota Bekasi - Putri Eka Sari; Pra Panca Bayu Candra; Vina Irfilian (An-Najat, 2024)
Jamu gendong is not only popular on the island of Java but can also be found on various other islands in Indonesia. Jamu gendong is a trditional medicine favored by the community. Although jamu gendong is not required to have distribution permit, the hygiene of its production process needs to be considered to ensure it is safe for consumption. Kunyit Asam is one of the most popular types among residents. The aim of this study is to determine the Total Plate Count (TPC) of bacteria in kunyit asam in RT 004 RW 012 Kayuringin Jaya, Bekasi City. Samples were taken from three sellers: seller 1, seller 2, and seller 3. The research stages included sample collection, sample preparation, and the total plate count bacterial test. The results of this study showed that for sample 1 and 2, the bacterial count was no more than 105 CFU/ml, while sample 3 had 2x105 CFU/ml. Based on these results, all three of jamu gendong samples meet the quality standards as per the Indonesian Food and Drug Authorithy Regulation Number 12 of 2014 for brewed herbs, with microbial contamination limits (TPC) ≤ 106 colonies/g.